Career guidance and industrial internship mechanisms and their effects on career readiness in technical and vocational education and training: a systematic literature review (2020–2026) - Zulia Saputra; Afdal Afdal; Miftahul Fikri; Nurfarhanah Nurfarhanah (Journal of Counseling, Education and Society, 2026)
The purpose of this comprehensive literature review critically synthesizes evidence on how industrial internships, work-based learning, and career guidance practices are experienced by students in vocational education and how these practices, in turn, influence students' career readiness and employability outcomes. The review process followed the PRISMA 2020 reporting framework standards. An initial pool of 401 documents was gathered from the Scopus database on 6 July 2026. The search was done using a Boolean string. After filtering out, 257 items were considered for further screening. After the screening and a full-text eligibility check against a structured inclusion/exclusion matrix and a FICO (Focus, Information, Context, Outcome) quality threshold (scored 0-8, with a minimum composite of 4 required for inclusion), 50 articles were deemed suitable for thematic synthesis using Thomas and Harden's thematic approach, with 10 leading examples being illustrated in depth. Screening and eligibility decisions were done by following one set of rules instead of using two raters who would check each other's work. This is a methodological limitation that is further discussed in the full text. Thematic synthesis grouped by three research questions shows that (1) work-based learning models are extensively used for converting vocational curricula into competences relevant to work; (2) personal attributes such as career self-confidence, career resilience, and clear vocational identity, combined with external factors like good teaching, industry exposure, and social support, not only influence students' career decisions but also their ability to find employment during internship; and (3) well-designed career guidance and counselling services, which are part of institutional industry link-and-match partnerships, seem to have a positive impact on school-to-work transition outcomes, although guidance services are still very much scattered and hardly evaluated in many countries. From a practitioner's perspective, the review suggests that formalizing internship supervision, incorporating career counseling into vocational courses at the beginning, and reinforcing the industry-school partnership mechanisms are some of the ways forward.